The campaign “De pé no chão também se aprende a ler” and the promotion of the educaction through the Popular Culture (Research, Society and Development, 2017)
The objective of this article is to present the different strategies of promotion of education by popular culture from the activities of the Campaign "De pé no chão também se aprende a ler". In order to reach this goal, we carried out a literature review considering classical authors in the discussion of the theme, such as José Willington Germano, Moacyr de Góes and Djalma Maranhão; Theses and dissertations; Other written sources, such as newspapers, and testimonials from people who have experienced the activities of the Campaign, such as alumni and teachers. After analyzed separately, the sources were crossed, following the guidelines of Paul Thompson, and allowed us to make some initial considerations about the Campaign. We realized that there were diverse strategies for the promotion of education through popular culture, ranging from the construction of squares, theaters and libraries, to the development of cultural circles, spaces for critical literacy, based on the Paulo Freire System. We consider, then, that the Campaign was not constituted in a homogeneous way, otherwise, it acted in a diversified way, with a view to achieving the goal of the dissemination of education through Popular Culture.